FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN SELFEFFICACY MENYUSUI DI RUANG BOUGENVILLE 2 RSUP DR. SARDJITO YOGYAKARTA - , NUR AINI FEBRIANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
World Health Organization (WHO), recommends continued breastfeeding until at least a period of 2 years, while weaning food supplement begins after 6 months of exclusive breastfeeding. The results of Indonesia Demographic and Health Survey shows that the coverage of exclusive breastfeeding in Indonesia reached 61.5% and Yogyakarta to reach 71%. However, 31.5% of mothers giving extra milk to infants aged 0-1 months. One way to achieve success in breastfeeding is self-efficacy. Objectives:For knowing factors that related with breastfeeding self-efficacyof mother in Bougenville 2 room of Dr. Sardjito Hospital. Methods: The study was descriptive correlational analytic using quantitative and cross sectional approach conducted on 75 mothers in the postpartum in room Bougenville 2 Dr. Sardjito Hospital. The questionnaire used was a questionnaire breastfeeding experience, the experience of seeing other people breastfeeding, support the husband / family, Postpartum Fatigue Scale (PFS), the Beck Depression Inventory (BDI) and the Breast-feeding Self-Efficacy Scale Short Form (BSESSF). Results: Number of children, level of education and experienceof breastfeeding related to breastfeeding self-efficacy with OR=4,160, 0,569 and 0,178. Conclusions: Number of children, level of education and experience of breastfeeding is a dominant factor associate with breast-feeding self-efficacy.